2006
DOI: 10.1002/pri.37
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists' perceptions and use of medical imaging information in practice

Abstract: Physiotherapists have access to some medical imaging information and perceive that this information could be valuable in patient care; however, not all therapists are confident in their ability to interpret this information. Curricula in entry-level physiotherapist educational programmes should include information about medical imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The participants in the current study had a positive attitude towards MI. Similarly, Little and Lazaro [ 28 ] reported that a cohort of USA-based physiotherapists had a positive perception of the utilisation of diagnostic imaging reports (DIR). However, the present study found a negative correlation between participants’ attitudes towards MI and years in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants in the current study had a positive attitude towards MI. Similarly, Little and Lazaro [ 28 ] reported that a cohort of USA-based physiotherapists had a positive perception of the utilisation of diagnostic imaging reports (DIR). However, the present study found a negative correlation between participants’ attitudes towards MI and years in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants in our study reported that they used imaging for musculoskeletal assessment. Little and Lazaro [ 28 ] reported that if available, 83.4% of their participants utilised DIR. The reader should note the difference between having the right to order MI and having access to DIR already processed through a physician’s directive [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…-76 ing on the specific clinic or hospital, when MSK imag-77 ing is needed, a PT requires a referral by another health-78 care professional. PTs in SA may demonstrate similar 79 practice barriers mentioned by PTs in previous stud-80 ies[3,7,15]. However, the practice of Saudi PTs in or-81 dering and interpreting DI has not been previously in-82 vestigated formally.…”
mentioning
confidence: 83%
“…The results of DI are utilized by radiologists and other healthcare professionals; physical therapists (PTs) in particular should be able to both identify the need for DI studies and use the results of imaging in patient management [ 2 ]. Knowledge of medical imaging material enables clinicians to understand, with greater depth and precision, the extent of a specific disease or condition during a patient’s evaluation, diagnosis, prognosis, and intervention [ 3 ]. In this context, the interest of PTs in DI is rising, as reflected in the increasing focus on it in physical therapy education, scientific papers, and books [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any comprehensive instrument that could be used to explore the nature of training, attitude, competence and utilisation of musculoskeletal imaging among physiotherapists. However, the following bodies of literature were found relevant in drafting the initial version of the instrument: physiotherapists’ perceptions and use of medical imaging information in practice (Little & Lazaro 2006); Ontario physiotherapists’ opinions on an expanded scope of practice and ordering diagnostic imaging (Chong et al 2015); and studies by Sak-Ocbina et al (2016), Boissonnault et al (2014) and Potter, Cairns and Stokes (2012). A step-by-step approach for the development, validation, pilot testing and implementation of an online profiling questionnaire was adopted from the works of Dizon et al (2011), Streiner and Norman (2008), Boynton (2004), Boynton and Greenhalgh (2004) and Andrews, Nonnecke and Preece (2003).…”
Section: Methodsmentioning
confidence: 99%